Study of the plasma behavior produced by a vacuum arc discharge for different cathode materials (2018)
Plasma-assisted techniques have been widely used for deposition of high quality thin films and metallurgical coatings. The glow plasma produced in the region between the electrodes and the chamber wall of a cathodic arc was modeled. The plasma behavior was characterized for different cathode materials that are commonly used in a cathodic arc deposition. The electron temperature, density, and electric potential were found to decrease as function of the distance from the spot region. However, the ion kinetic energy tends to increase due to the acceleration of the ions coming from the bulk region. Our results show that the cathodic arc is not directly affected by the plasma potential of the glow plasma and that the cathode material has an important influence on the plasma behavior, mainly because of the electrical and thermal conductivity of each material.